2017
DOI: 10.1097/rct.0000000000000598
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced Magnetic Resonance Imaging of Ocular Melanoma as a Tool to Predict Metastatic Potential

Abstract: Dynamic contrast-enhanced magnetic resonance imaging has the potential to differentiate orbital melanomas with metastatic and nonmetastatic spread. Thus, DCE-MRI has the potential to be an in vivo imaging technique to predict early which patients are prone to metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Studies comparing DCE-MRI derived parameters with the metastatic potential of individual tumors are sparse. However, in a study involving 13 patients with ocular melanoma, Wei et al [46] found that metastatic tumors had lower K trans than non-metastatic tumors, in line with our experiments. [26], Øvrebø et al [36], and Øvrebø et al [45].…”
Section: K Trans Reflects Metastatic Potentialsupporting
confidence: 91%
“…Studies comparing DCE-MRI derived parameters with the metastatic potential of individual tumors are sparse. However, in a study involving 13 patients with ocular melanoma, Wei et al [46] found that metastatic tumors had lower K trans than non-metastatic tumors, in line with our experiments. [26], Øvrebø et al [36], and Øvrebø et al [45].…”
Section: K Trans Reflects Metastatic Potentialsupporting
confidence: 91%
“…DCE-MRI implies the sequential (multiphasic) acquisition of multiple T1-weighted sequences (total of 50–95 temporal points) with high temporal resolution (acquisition time 3–9 s), before (5–9 baseline dynamic acquisitions), during and after i.v. administration of Gd-based contrast agents [ 26 , 42 , 43 ]. The tumor perfusion can be graphically represented in the shape of time-intensity curves (TIC) obtained by drawing a region of interest (ROI) in the lesion.…”
Section: Imaging Methods In the Diagnosis Of Uveal Melanomamentioning
confidence: 99%
“…Quantitative pharmacokinetic parameters, mirroring tumor microcirculation, can be obtained as well using dedicated postprocessing tools. The acquired images may, however, be susceptible to misregistration artifacts related to eye motion [ 26 , 42 , 43 ]. DCE-MRI in association with DWI can be useful to distinguish benign from malignant orbital lesions [ 43 ].…”
Section: Imaging Methods In the Diagnosis Of Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Although UM was studied with MRI in the late 1980s, 27 and different studies have shown promising steps towards the clinical application of MRI for UM, the advances towards higher field strengths have enabled the more routine clinical application of MRI for UM over the last decade. 25,[28][29][30][31][32] Our institution is the National Reference Centre for UM in The Netherlands, and so is a main centre for developing and assessing new imaging techniques for UM. Over the past 5 years, different hardware, software and data acquisition techniques for MRI of UM patients have been developed.…”
Section: Introductionmentioning
confidence: 99%